Oxidative Stress Induced Cell Damage and Antioxidant Enzyme Response in Human Lymphocytes - Dua, Anita (International Journal of Pharmaceutical & Biological Archive, 2017)
Human lymphocytes were subjected to oxidative stress by exposing to hydrogen peroxide at concentrations varying from 0-250Î¼M for time duration of 0-24h to evaluate cell viability. Trypan blue dye exclusion test indicated a loss of Ë‚5% cell viability on incubation with hydrogen peroxide for 24h; however MTT assay signified a decline of 55% activity after 12h or long with 200Î¼M concentration. Redox status and activities of antioxidant enzymes were examined after incubation with hydrogen peroxide up to 200Î¼M for 4h. Reduced glutathione level decreased with concentration dependent increase in lipid peroxidation, measured as MDA produced. Increase in LDH leakage from the cells with increasing hydrogen peroxide concentration in medium indicated considerable cell membrane damage. SOD and catalase activities increased at lower concentration of 50Î¼M but at higher stress, a decline in activities of SOD, catalase and GST was observed. GPx increased with increasing hydrogen peroxide in incubation medium. The study shows that redox status declines and cell membranes become leaky with increasing oxidative stress. Antioxidant enzymes except GPx decrease under higher stress conditions.